Micro-expansive and high-impedance composite admixture for self-filling concrete and preparation method of micro-expansive and high-impedance composite admixture

By developing a micro-expanding, high-impedance composite blend for self-filled concrete, the problems of shrinkage and corrosion resistance of self-filled concrete are solved, and better crack resistance, permeability and high resistivity characteristics are achieved, and the service life of concrete is extended.

CN119661138APending Publication Date: 2025-03-21CHINA RAILWAY SIYUAN SURVEY & DESIGN GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411923128.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The amount of gelling material used in the material composition of self-filled concrete is large, the fine powder particles are many, and the water-gluing ratio is small, resulting in significant shrinkage and is susceptible to stray current corrosion and groundwater erosion in urban rail projects.

Method used

A micro-expanded, high-impedance composite blend for self-filled concrete is developed, including slag powder, fly ash, silicon powder, aluminum powder, calcium oxide, magnesium oxide, viscosity modifier and impedance. Through the multi-stage expansion agent regulation and the use of impedance agent, the concrete's crack resistance, chloride ion penetration and high resistivity are improved.

Benefits of technology

It effectively reduces the shrinkage of self-filled concrete, improves its crack resistance and chloride ion permeability, and enhances its resistance to stray current corrosion, extends the service life of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a micro-expansion and high-impedance composite admixture for self-filling concrete and a preparation method of the micro-expansion and high-impedance composite admixture, and belongs to the technical field of concrete admixtures. The micro-expansive and high-impedance composite admixture for the self-filling concrete comprises the following raw materials in parts by weight: 45 parts of slag powder, 35 parts of fly ash, 30 parts of silicon powder, 16-48 parts of an expanding agent, 8 parts of a viscosity modifier and 8-24 parts of an impedance agent, wherein the expanding agent is a mixture formed by aluminum powder, calcium oxide and magnesium oxide; the dosage of the micro-expansive and high-impedance composite admixture for the self-filling concrete is 20 wt.%-30 wt.% of the dosage of a cementing material in the self-filling concrete. The composite admixture can enable the self-filling concrete to have the characteristics of good crack resistance, chloride ion permeation resistance, high resistivity and the like, has outstanding advantages in the field of urban rail transit, and can remarkably inhibit shrinkage cracking of the self-filling concrete and corrosion of the self-filling concrete under stray current and erosion media.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete admixtures, and in particular to a micro-expansion, high-impedance composite admixture for self-filling concrete and a preparation method thereof. Background Art

[0002] In recent years, urban rail transit has developed rapidly as a key infrastructure construction in the transportation field. Among them, self-filling concrete has been widely used in the field of urban rail transit due to its convenient construction and strong adaptability to structural sections.

[0003] For example, the Chinese invention patent with publication number CN111170682A provides a self-filling concrete for railway tunnel lining, which is made by mixing a cementing component, an anti-cracking component, a viscosity regulating component, a hydration temperature rise suppression component, an anti-corrosion component, an anti-freezing component, a water reducing component, aggregates, and water in a forced mixer in a certain proportion. The concrete has excellent self-filling properties, gap passing properties, dynamic stability, high robustness, and crack resistance under micro-vibration.

[0004] However, due to the large amount of cementitious materials used in the composition of self-filling concrete, the large amount of fine powder particles and the small water-binder ratio, the shrinkage is more significant than that of ordinary concrete. In addition, due to the special environment of urban rail projects, they may be subject to long-term stray current corrosion and penetration of various corrosive media in groundwater during their service, which poses a great threat to the safety of urban rail concrete structures.

[0005] To address the problem of large shrinkage in self-filling concrete, the commonly used solutions are to add expansive agents or shrinkage reducers to improve the shrinkage characteristics of concrete, reduce shrinkage by changing the shrinkage characteristics of the capillary pores in the cement paste, and add substances with micro-expansion reactions to compensate for the shrinkage of the cement paste, thereby controlling the shrinkage degree of the cement paste and achieving the purpose of reducing shrinkage and improving crack resistance.

[0006] For example, the Chinese invention patent with publication number CN118026610A provides a micro-expansive concrete and its production process. The invention enhances the mechanical meshing force between the synergistic expansive agent and the compound expansive agent, as well as the expansion amount of the concrete after hardening, inhibits the early plastic shrinkage of the concrete, and thus improves its anti-cracking effect. However, the preparation process of the invention is relatively complicated, and a compound expansive agent with a core-shell structure is required, which limits its applicability. In addition, in the application scenario of urban rail transit, the formation process of shrinkage cracking is long-term, and only suppressing the shrinkage of a certain stage is difficult to meet the actual application needs. In addition, this solution still does not solve the problems of stray current corrosion and penetration of corrosive media.

[0007] The concrete currently used in this field still has shrinkage cracking problems in actual applications. In order to solve the problems of stray current corrosion and medium erosion during the service of self-filling concrete, fly ash, slag and other mineral admixtures are usually used to optimize the concrete pore structure, improve impermeability and impedance. However, excessive admixture will greatly reduce the strength and working performance of concrete, and is not conducive to the long-term durability of self-filling concrete.

[0008] In summary, how to reduce the shrinkage of self-filling concrete and improve the impedance has important practical significance for expanding the application scope of self-filling concrete. Therefore, it is urgent to develop a composite admixture for self-filling concrete to provide material guarantee for the large-scale engineering application of self-filling concrete. Summary of the invention

[0009] In view of the above-mentioned defects of the prior art, in the first aspect of the present invention, a micro-expansion, high-impedance composite admixture for self-filling concrete having good crack resistance, resistance to chloride ion penetration and high resistivity is provided, comprising the following raw materials in parts by weight: 45 parts of slag powder, 35 parts of fly ash, 30 parts of silica powder, 16-48 parts of expansion agent, 8 parts of viscosity modifier, 8-24 parts of impedance agent; wherein the expansion agent is a mixture of aluminum powder, calcium oxide and magnesium oxide; the amount of micro-expansive and high-impedance composite admixture for self-filling concrete is 20 wt.%-30 wt.% of the amount of cementitious material in the self-filling concrete.

[0010] Preferably, the slag powder is a molten material obtained by smelting pig iron in a blast furnace and mainly composed of aluminosilicates, which has a latent hydraulic material after being cooled and granulated; the bulk density of the slag powder is ≤1.2×10 3 kg / m 3 , the maximum particle size is ≤50mm, and the mass fraction of particles with a diameter greater than 10 mm is ≤8%.

[0011] Further preferably, the chemical composition of the slag powder is as follows: CaO is 40 wt.%, SiO 2 35 wt.%,Al 2 O 3 12 wt.%, SO 3 It is 9 wt.%, and other types of oxides are 4 wt.%.

[0012] Preferably, the fly ash is powder collected from the gas in the pulverized coal furnace channel of a power plant; the fineness of the fly ash (residue on a 45 μm square sieve) is ≤12%, the water requirement ratio is ≤95%, and the loss on ignition is 5.0%.

[0013] Further preferably, the SiO in the fly ash 2 、Al 2 O3 and Fe 2 O 3 The total mass fraction is ≥50%.

[0014] Preferably, the silicon powder is a powder material with amorphous silicon dioxide as the main component obtained by collecting dust discharged through the flue during the smelting of ferrosilicon alloy or industrial silicon; the specific surface area of ​​the silicon powder is ≥15 m 2 / g.

[0015] Further preferably, the SiO in the silicon powder 2 The quality fraction is ≥85%.

[0016] Preferably, the viscosity modifier is a material added to concrete to improve the stability, viscosity and water retention of the concrete mixture; the viscosity ratio of the viscosity modifier is ≥150%, and the water consumption sensitivity is ≥12 kg / m 3 .

[0017] Preferably, the content of magnesium oxide in the expander is ≤40 wt.%.

[0018] Further preferably, the expansion agent is a mixture of aluminum powder, calcium oxide and magnesium oxide in a mass ratio of 3:7:6.

[0019] Preferably, the impedance agent is a mixture of polyamine, imidazoline quaternary ammonium salt and silane waterproofing agent.

[0020] Further preferably, the mass ratio of the polyamine, imidazoline quaternary ammonium salt and silane waterproofing agent is 2:1:1.

[0021] In a second aspect of the present invention, a method for preparing the micro-expansion, high-impedance composite admixture for self-filling concrete according to the first aspect of the present invention is provided, which has a convenient process and comprises the following steps: Slag powder, fly ash, silica powder, expansion agent, viscosity modifier and impedance agent are prepared according to proportion, mixed so that the raw materials are evenly dispersed, and a micro-expansion and high-impedance composite admixture for self-filling concrete is obtained.

[0022] Based on the above technical scheme, the design concept of the present invention is that the expansion performance of the micro-expansion, high-impedance composite admixture for self-filling concrete is regulated through different stages, the first stage is provided by the aluminum powder micro-expansion agent, the second stage is provided by the calcium oxide expansion agent, and the third stage is provided by the magnesium oxide expansion agent. The three-stage regulation mechanism of self-filling concrete is as follows: (1) The expansion of the first stage of self-filling concrete is mainly provided by the above-mentioned aluminum powder expansion agent. The mechanism of aluminum powder as a self-filling concrete expansion agent can be summarized as the following steps: 1. Aluminum powder and water in concrete undergo oxidation reaction to produce hydrogen; 2. The produced hydrogen will gradually be released in the concrete; tiny bubbles are generated when hydrogen is released, and the bubbles diffuse into the concrete; 4. After a large number of tiny bubbles are formed, the volume of concrete will expand; (2) The expansion of the second stage of self-compacting concrete is mainly provided by the above-mentioned calcium oxide expansion agent. Calcium oxide reacts with water to form calcium hydroxide. While the solid phase volume increases, the local accumulation of hydration products leads to an increase in the pore volume, thereby causing the volume expansion of the paste in the self-compacting concrete. (3) The expansion of the third stage of self-filling concrete is mainly provided by the above-mentioned magnesium oxide expansion agent. Magnesium oxide reacts with water in concrete to produce magnesium hydroxide. During the hydration reaction, the magnesium hydroxide produced has a large specific surface area, so the volume of magnesium oxide before hydration is large, which causes the volume expansion of the self-filling concrete.

[0023] In the application environment designed by the present invention, there is a widespread phenomenon of stray current corrosion in subway projects, which will cause serious corrosion to the buried metal along the track and the steel bars in the concrete structure, thus posing a great threat to the safety of the concrete structure. Therefore, the high impedance performance of the composite admixture is mainly for facing the stray current of the subway project. The high impedance performance of the composite admixture is achieved by an impedance agent. By adding three components, polyamine, imidazoline quaternary ammonium salt and silane waterproofing agent, into concrete, as a migration type rust inhibitor, it can directly participate in the interfacial chemical reaction on the one hand, accelerate the formation of a passivation film or adsorption film on the surface of the steel bar, thereby inhibiting the anodic or cathodic electrochemical reaction between the concrete and the steel bar interface; on the other hand, it is dispersed in the concrete, has a good adsorption effect on chloride ions, and blocks the source of its erosion. Thereby solving the problem of stray current corrosion and penetration of corrosive media.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects: The invention provides a micro-expansion, high-impedance composite admixture for self-filling concrete. Aluminum powder, calcium oxide and magnesium oxide are used as expansion agents. In the first stage, aluminum powder reacts chemically with water to generate hydrogen, and the hydrogen is released to form fine bubbles, which causes the concrete volume to expand. In the second stage, calcium oxide reacts chemically with water to generate calcium hydroxide, which generates the expansion effect of calcium hydroxide crystals and provides micro-expansion regulation. In the third stage, magnesium oxide reacts chemically with water to generate magnesium hydroxide, which generates the expansion effect of magnesium hydroxide crystals and causes the concrete volume to expand. The shrinkage problem of the self-filling concrete is solved in multiple stages, and the concrete has good crack resistance, chloride ion penetration resistance and high resistivity characteristics.

[0025] The present invention provides a method for preparing a micro-expansion, high-impedance composite admixture for self-filling concrete, which has the advantages of being simple and quick and has good application prospects under various working conditions. DETAILED DESCRIPTION

[0026] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0027] In the following embodiments: The composite admixtures and mix proportions of self-compacting concrete are designed according to Q / CR 596-2017 "Self-compacting concrete for CRTS III type ballastless track of high-speed railway" and GB / T23439-2017 "Concrete expansion agent".

[0028] Among them, the coarse aggregate is clean crushed stone, crushed pebbles or pebbles with reasonable grading, good particle shape, uniform and firm texture and small linear expansion coefficient. The coarse aggregate is mixed with secondary aggregate, with the maximum nominal particle size not exceeding 20mm, the content of needle-like particles not exceeding 5%, the mud content not exceeding 0.5%, and other properties shall comply with the provisions of TB / T 3275-2018 "Railway Concrete".

[0029] Fine aggregate should preferably be clean natural medium-coarse river sand with reasonable grading, uniform and solid texture, low water absorption and small porosity. Machine-made sand produced by special units can also be used. The fineness modulus of fine aggregate is 2.1-2.8, the mud content is not more than 2.0%, and other properties should comply with the provisions of TB / T 3275-2018 "Railway Concrete".

[0030] The performance of mixing water complies with the requirements of JGJ 63-2006 "Standard for Water for Concrete".

[0031] The slag powder used is a molten material with aluminosilicate as the main component obtained by smelting pig iron in a blast furnace. After cooling and granulation, it has a potential hydraulic material with the following chemical composition: CaO is 40 wt.%, SiO 2 35 wt.%,Al 2 O 3 12 wt.%, SO 3 9 wt.%, and the other types of oxides are 4 wt.%. Its bulk density is ≤1.2×10 3 kg / m 3 , the maximum particle size is ≤50 mm, and the mass fraction of particles with a particle size greater than 10 mm is ≤8%.

[0032] The fly ash used is the powder collected from the gas in the pulverized coal furnace of the power plant, in which SiO2 、Al 2 O 3 and Fe 2 O 3 The total mass fraction of fly ash is ≥50%; the fineness of fly ash (45 μm square hole sieve residue) is ≤12%, the water requirement ratio is ≤95%, and the loss on ignition is 5.0%.

[0033] The silicon powder used is a powder material with amorphous silicon dioxide as the main component obtained by collecting dust discharged through the flue during the smelting of ferrosilicon alloy or industrial silicon. 2 The mass fraction of silicon powder is ≥85%; the specific surface area of ​​silicon powder is ≥15m 2 / g.

[0034] The expansion agent used is a mixture of aluminum powder, calcium oxide and magnesium oxide in a mass ratio of 3:7:6.

[0035] The viscosity modifier used is a material added to concrete to improve the stability, viscosity and water retention of the concrete mixture; the viscosity ratio of the viscosity modifier is ≥150%, and the water consumption sensitivity is ≥12 kg / m 3 .

[0036] The impedance agent used is a mixture of polyhexamethylenediamine, stearic acid imidazoline quaternary ammonium salt, and silane waterproofing agent, wherein the polyamine is 4 parts, the imidazoline quaternary ammonium salt is 2 parts, and the silane waterproofing agent is 2 parts.

[0037] Example 1 This embodiment provides a micro-expansion, high-impedance composite admixture for self-filling concrete (hereinafter referred to as composite admixture), comprising the following raw materials in parts by weight: 45 parts of slag powder, 35 parts of fly ash, 30 parts of silica powder, 16 parts of expansion agent, 8 parts of viscosity modifier, 8 parts of impedance agent; wherein the expansion agent is a mixture of aluminum powder, calcium oxide and magnesium oxide. The composite admixture is mixed with 837 parts of coarse aggregate, 805 parts of fine aggregate, 325 parts of cement and 165 parts of water to form self-compacting concrete.

[0038] Example 2 This embodiment provides a micro-expansion, high-impedance composite admixture for self-filling concrete, comprising the following raw materials in parts by weight: 45 parts of slag powder, 35 parts of fly ash, 30 parts of silica powder, 24 parts of expansion agent, 8 parts of viscosity modifier, 12 parts of impedance agent; wherein the expansion agent is a mixture of aluminum powder, calcium oxide and magnesium oxide. The composite admixture is mixed with 837 parts of coarse aggregate, 805 parts of fine aggregate, 313 parts of cement and 165 parts of water to form self-compacting concrete.

[0039] Example 3 This embodiment provides a micro-expansion, high-impedance composite admixture for self-filling concrete, comprising the following raw materials in parts by weight: 45 parts of slag powder, 35 parts of fly ash, 30 parts of silica powder, 32 parts of expansion agent, 8 parts of viscosity modifier, 16 parts of impedance agent; wherein the expansion agent is a mixture of aluminum powder, calcium oxide and magnesium oxide. The composite admixture is mixed with 837 parts of coarse aggregate, 805 parts of fine aggregate, 301 parts of cement and 165 parts of water to form self-compacting concrete.

[0040] Example 4 This embodiment provides a micro-expansion, high-impedance composite admixture for self-filling concrete, comprising the following raw materials in parts by weight: 45 parts of slag powder, 35 parts of fly ash, 30 parts of silica powder, 40 parts of expansion agent, 8 parts of viscosity modifier, 20 parts of impedance agent; wherein the expansion agent is a mixture of aluminum powder, calcium oxide and magnesium oxide. The composite admixture is mixed with 837 parts of coarse aggregate, 805 parts of fine aggregate, 289 parts of cement and 165 parts of water to form self-compacting concrete.

[0041] Example 5 This embodiment provides a micro-expansion, high-impedance composite admixture for self-filling concrete, comprising the following raw materials in parts by weight: 45 parts of slag powder, 35 parts of fly ash, 30 parts of silica powder, 48 parts of expansion agent, 8 parts of viscosity modifier, 24 parts of impedance agent; wherein the expansion agent is a mixture of aluminum powder, calcium oxide and magnesium oxide. The composite admixture is mixed with 837 parts of coarse aggregate, 805 parts of fine aggregate, 325 parts of cement and 165 parts of water to form self-compacting concrete.

[0042] Comparative Example 1 This embodiment provides a composite admixture, comprising the following raw materials in parts by weight: 45 parts of slag powder, 35 parts of fly ash, 30 parts of silica powder, 0 parts of expansion agent, 8 parts of viscosity modifier, 8 parts of impedance agent; wherein the expansion agent is a mixture of aluminum powder, calcium oxide and magnesium oxide. The composite admixture is mixed with 837 parts of coarse aggregate, 805 parts of fine aggregate, 341 parts of cement and 165 parts of water to form self-compacting concrete.

[0043] Comparative Example 2 This embodiment provides a composite admixture, comprising the following raw materials in parts by weight: 45 parts of slag powder, 35 parts of fly ash, 30 parts of silica powder, 16 parts of expansion agent, 8 parts of viscosity modifier, and 0 parts of impedance agent; wherein the expansion agent is a mixture of aluminum powder, calcium oxide, and magnesium oxide. The composite admixture is mixed with 837 parts of coarse aggregate, 805 parts of fine aggregate, 333 parts of cement, and 165 parts of water to form self-compacting concrete.

[0044] Test Example 1 This test example studies the comprehensive performance of the composite admixture in practical applications. Table 1 shows the self-filling concrete mix design of the above embodiment and comparative example.

[0045] Table 1: Self-filling concrete mix design (parts by weight)

[0046] The microstrain of the self-filling concrete was tested according to the method provided in GB / T 50082-2009 “Standard for Test Methods of Long-term Performance and Durability of Concrete”. The test results are shown in Table 2.

[0047] Table 2: Microstrain of self-compacting concrete

[0048] The above test results show that: (1) According to Examples 1-5, as the amount of the expansive agent increases, the microstrain of the self-filling concrete gradually increases, and the early microstrain growth rate accelerates, indicating that the expansive agent in the composite admixture has a good early expansion effect and provides the first and second stage expansion for the concrete; (2) According to Examples 1-5 and Comparative Example 1, without the addition of the expansive agent, the microstrain of the self-filling concrete gradually increases with age, indicating that the expansive agent in the composite admixture can provide the third stage expansion for the concrete. The above test results meet the design expectations and achieve the purpose of the present invention.

[0049] According to the method steps provided in GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Concrete", the electric flux, chloride ion diffusion coefficient and resistivity of self-filling concrete were tested. The test results are shown in Table 3.

[0050] Table 3: Impedance properties of self-compacting concrete

[0051] The above test results show that: according to Examples 1-5 and Comparative Example 2, as the amount of the impedance agent increases, the electric flux and chloride ion diffusion coefficient of the self-filling concrete gradually decrease, and the resistivity gradually increases. The self-filling concrete has good resistance to chloride ion permeability and high resistivity characteristics, and can be widely used in subway rail transit projects.

[0052] In summary, the present invention provides a micro-expansion, high-impedance composite admixture for self-filling concrete, with aluminum powder, calcium oxide, and magnesium oxide as expansion agents, in the first stage, aluminum powder reacts with water to produce hydrogen, and hydrogen is released to form fine bubbles, resulting in the expansion of the concrete volume; in the second stage, calcium oxide reacts with water to produce calcium hydroxide, producing the expansion effect of calcium hydroxide crystals, providing micro-expansion regulation; in the third stage, magnesium oxide reacts with water to produce magnesium hydroxide, producing the expansion effect of magnesium hydroxide crystals, resulting in the expansion of the concrete volume; the shrinkage problem of self-filling concrete is solved in multiple stages. And the three components of polyamine, imidazoline quaternary ammonium salt and silane waterproofing agent are added to concrete as a migration type rust inhibitor, which can directly participate in the interface chemical reaction on the one hand, accelerate the formation of a passivation film or adsorption film on the surface of the steel bar, thereby inhibiting the anode or cathode electrochemical reaction between the concrete and the steel bar interface; on the other hand, it is dispersed in the concrete, has a good adsorption effect on chloride ions, blocks the source of its erosion, thereby solving the problem of stray current corrosion and erosion medium penetration. The micro-expansion, high-impedance composite admixture for self-filling concrete of the present invention has good crack resistance, resistance to chloride ion penetration and high resistivity characteristics.

[0053] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A micro-expansive, high-impedance composite admixture for self-filling concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 45 parts of slag powder, 35 parts of fly ash, 30 parts of silicon powder, 16-48 parts of expansion agent, 8 parts of viscosity modifier and 8-24 parts of impedance agent; wherein the expansion agent is a mixture of aluminum powder, calcium oxide and magnesium oxide; and the amount of micro-expansion and high-impedance composite admixture for self-filling concrete is 20 wt.%-30 wt.% of the amount of cementitious material in the self-filling concrete.

2. The micro-expansive, high-impedance composite admixture for self-filling concrete according to claim 1, characterized in that: The slag powder is a molten material with aluminosilicate as the main component obtained by smelting pig iron in a blast furnace. After being cooled and granulated, it has a potential hydraulic material. The bulk density of the slag powder is ≤1.2×10 3 kg / m 3 , the maximum particle size is ≤50 mm, and the mass fraction of particles with a particle size greater than 10 mm is ≤8%.

3. The micro-expansive, high-impedance composite admixture for self-filling concrete according to claim 2, characterized in that: The chemical composition of the slag powder is as follows: 40 wt.% of CaO, 35 wt.% of SiO2, 12 wt.% of Al2O3, 9 wt.% of SO3, and 4 wt.% of other types of oxides.

4. The micro-expansive, high-impedance composite admixture for self-filling concrete according to claim 1, characterized in that: The fly ash is powder collected from the gas in the pulverized coal furnace channel of a power plant; the fineness of the fly ash (residue on a 45 μm square sieve) is ≤12%, the water requirement ratio is ≤95%, and the loss on ignition is 5.0%.

5. The micro-expansive, high-impedance composite admixture for self-filling concrete according to claim 4, characterized in that: The total mass fraction of SiO2, Al2O3 and Fe2O3 in the fly ash is ≥50%.

6. The micro-expansive, high-impedance composite admixture for self-filling concrete according to claim 1, characterized in that: The silicon powder is a powder material with amorphous silicon dioxide as the main component obtained by collecting dust discharged through the flue during the smelting of ferrosilicon alloy or industrial silicon; the specific surface area of ​​the silicon powder is ≥15 m 2 / g.

7. The micro-expansive, high-impedance composite admixture for self-filling concrete according to claim 6, characterized in that: The mass fraction of SiO2 in the silicon powder is ≥85%.

8. The micro-expansive, high-impedance composite admixture for self-filling concrete according to claim 1, characterized in that: The viscosity modifier is a material added to concrete to improve the stability, viscosity and water retention of concrete mixture; the viscosity ratio of the viscosity modifier is ≥150%, and the water consumption sensitivity is ≥12 kg / m 3 .

9. The micro-expansive, high-impedance composite admixture for self-filling concrete according to claim 1, characterized in that: The content of magnesium oxide in the expansion agent is ≤40 wt.%; the resistance agent is a mixture of polyamine, imidazoline quaternary ammonium salt and silane waterproofing agent.

10. A method for preparing a micro-expansive, high-impedance composite admixture for self-filling concrete as described in any one of claims 1 to 9, comprising the following steps: preparing slag powder, fly ash, silica powder, expansion agent, viscosity modifier, and impedance agent according to proportions, mixing them so that the raw materials are evenly dispersed, and obtaining the micro-expansive, high-impedance composite admixture for self-filling concrete.

Citation Information

Patent Citations

  • Self-filling concrete for railway tunnel lining

    CN111170682A

  • Micro-expansive concrete and production process thereof

    CN118026610A